Seeing Themselves: Jean Barman’s French Canadians, Furs, and Indigenous Women in the Making of the Pacific Northwest as a Resource for the Region’s People - Nation-Knapper, Stacy (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2016)
Dr. Barman’s award-winning study is a resource to the Indigenous and non-Indigenous people of the Columbia River Plateau and the Pacific Northwest, an environmentally and culturally diverse region that now encompasses two countries, two provinces, three states, and many Indigenous communities. For Indigenous communities of the region, French Canadians, Furs, and Indigenous Women in the Making of the Pacific Northwest provides an important context of colonialism, global economics, and the complicated nature of cross-cultural encounters. For non-Indigenous communities, the book also encourages an appreciation for the complexities of history often overlooked by celebratory histories of colonization. French Canadians, Furs, and Indigenous Women in the Making of the Pacific Northwest is a resource in which people see themselves and their families in a complicated, accessible, and inspiring story of the past.